Certificação de grãos no estado de Mato Grosso: estudo de caso em uma empresa produtora e exportadora de soja - Redivo, Arlete (Universidade Federal de São Carlos, 2010)
Large sized companies in the grain segment are trying to make their products stand out in the market. In order to do so, they seek for certification to meet the expectations of consumer markets, regarding the intrinsic quality of the grains traded, aiming to ensure health and socioenvironmental responsibility. Worries related to the environment expressed by the rejection of consumer class in acquiring goods that throughout their life span may cause environmental harm and the trends resulting from changes in the standards of competition, derived from the new scenario of increasingly open and globalized economy, as well as the lack of quality certificates for those products, justify such market behavior. Thus, this study aimed to evaluate the certification programs used by a company that acts as a producer and exporter of soybeans in the state of Mato Grosso, highlighting the benefits and difficulties faced by the organization to obtain and maintain such programs once they were implemented. The proposed research approach was qualitative, exploratory, carrying out a case study, which used a single case, and the information was gathered from those responsible for process of implementation and maintenance of grain certification. Through the development of the research, it was possible to observe the certification process of grains as an instrument that may be compatible with the diversification of production and increase in the interactions established between the producers and the actors involved in the trade and export of grains. The main contributions of this study were the noticed benefits in the implementation of certificates and seals that have the role of catalyzing the changes in the production process with credibility and commitment to continuous improvement. On the other hand, in order to reduce the identified difficulties, what we proposed are some criteria and procedures that could be included in the adoption of the certificate to ease the implementation process.
Keywords: Engenharia de produção; Certificação; Soja; Aspectos econômicos; Certification of grains; Soybeans; Benefits; Difficulties; ENGENHARIAS::ENGENHARIA DE PRODUCAO